(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The estimation of the performance of Wave Energy Converter (WEC) arrays of the type of simple floaters operating in nearshore and coastal areas, characterized by variable bottom topography, is important for the estimation of the wave power absorption and determination of the operational characteristics of the system and could significantly contribute to the efficient design and layout of WEC farms. For this purpose, full 3D models based on Boundary Element Method have been developed, supporting the systematic use for optimization studies. Apart from WEC arrays in nearshore and coastal regions a promising possibility is the installation at the exposed side of port breakwaters with significant energy potential. In this work, the analysis of the above system is extended to the prediction of WEC performance in multichromatic incident waves under latching control strategy using a time-domain simulator, showing improvement of performance in particular conditions.